The Role of Memorable Educational Tourism Experience in Shaping Revisit Intention: The Moderating Effects of Novelty Seeking and Overtourism Sensitivity (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study contributes theoretically by developing a conditional dual-moderation model that explains when and for whom MTE effectively translates into revisit intention, particularly within educational tourism contexts.. Method: A quantitative approach was employed using a survey method, with data collected from 319 respondents who had previously visited tourism destinations in West Java. Data were analyzed using Moderation Regression Analysis (MRA) with Hayes PROCESS Model 2 in SPSS to examine both direct and moderating effects. Results: The results indicate that MTE has a positive effect on revisit intention, suggesting that memorable experiences encourage tourists to consider revisiting the same destination. However, the strength of this relationship varies depending on individual characteristics and perceptions. Novelty seeking weakens the relationship between MTE and revisit intention, indicating that tourists with a strong preference for new experiences are less likely to revisit the same destination despite having memorable experiences. In contrast, overtourism sensitivity influences how tourists evaluate the feasibility of revisiting, as concerns about crowding and destination conditions shape future travel considerations. Novelty: This study contributes by integrating novelty seeking and overtourism sensitivity as simultaneous moderators in the MTE–revisit intention relationship, offering a more comprehensive explanation of how memorable experiences translate into future behavioral intentions in tourism contexts.